The COSMOS-Web ring: In-depth characterization of an Einstein ring lensing system at z ∼ 2 - Mercier, W.; Shuntov, M.; Gavazzi, R.; Nightingale, J. W.; Arango, R.; Ilbert, O.; Amvrosiadis, A.; Ciesla, L.; Casey, C. M.; Jin, S.; Faisst, A. L.; Andika, I. T.; et al. (Astronomy & Astrophysics, 2024)
Aims. We provide an in-depth analysis of the COSMOS-Web ring, an Einstein ring at z ≈ 2 that we serendipitously discovered during the data reduction of the COSMOS-Web survey and that could be the most distant lens discovered to date. Methods. We extracted the visible and near-infrared photometry of the source and the lens from more than 25 bands. We combined these observations with far-infrared detections to study the dusty nature of the source and we derived the photometric redshifts and physical properties of both the lens and the source with three different spectral energy distribution (SED) fitting codes. Using JWST/NIRCam images, we also produced two lens models to (i) recover the total mass of the lens, (ii) derive the magnification of the system, (iii) reconstruct the morphology of the lensed source, and (iv) measure the slope of the total mass density profile of the lens. Results. We find the lens to be a very massive elliptical galaxy at z = 2.02 ± 0.02 with a total mass within the Einstein radius of Mtot(<θEin = (3.66 ± 0.36) × 1011 M⊙ and a total stellar mass of M⋆ = 1.37−0.11+0.14 × 1011 M⊙. We also estimate it to be compact and quiescent with a specific star formation rate below 10−13 yr. Compared to stellar-to-halo mass relations from the literature, we find that the total mass of the lens within the Einstein radius is consistent with the presence of a dark matter (DM) halo of total mass Mh = 1.09−0.57+1.46 × 1013 M⊙. In addition, the background source is a M⋆ = (1.26 ± 0.17) × 1010 M⊙ star-forming galaxy (SFR ≈ (78 ± 15) M⊙ yr) at z = 5.48 ± 0.06. The morphology reconstructed in the source plane shows two clear components with different colors. Dust attenuation values from SED fitting and nearby detections in the far infrared also suggest that the background source could be at least partially dust-obscured. Conclusions. We find the lens at z ≈ 2. Its total, stellar, and DM halo masses are consistent within the Einstein ring, so we do not need any unexpected changes in our description of the lens such as changing its initial mass function or including a non-negligible gas contribution. The most likely solution for the lensed source is at z ≈ 5.5. Its reconstructed morphology is complex and highly wavelength dependent, possibly because it is a merger or a main sequence galaxy with a heterogeneous dust distribution.